Genomic characterization of avian and neoavian orthoreoviruses detected in pheasants - Farkas, Szilvia L.; Varga-Kugler, Renáta; Ihász, Katalin; Marton, Szilvia; Gál, János; Palya, Vilmos; Bányai, Krisztián (Virus research, 2021)
•Whole genome sequences and phylogenetic analyses of novel pheasant orthoreoviruses are presented.•Reo/HUN/Pheasant/216/2015 is a reassortant strain showing genetic relationship with turkey, chicken and partridge reoviruses.•Strain D1996/2/1 is distantly related to any currently known avian origin orthoreoviruses. Avian reoviruses are well-known pathogens seriously affecting the productivity of poultry industry. Game birds represent a small segment of the agricultural sector and much remained to be learnt about factors affecting productivity. Here we show that reovirus infections might occur in pheasants and demonstrate that reoviruses of pheasants are of diverse origin. The complete or coding-complete genomic sequences of two Hungarian reovirus strains, D1996/2/1 and Reo/HUN/Pheasant/216/2015, have been determined in this study. The strain D1996/2/1 was isolated in 2012 from birds with gizzard erosion, whereas the other strain was isolated in 2015 from diarrheic pheasant poults. Phylogenetic analyses showed that none of the Hungarian isolates shared common origin with a pheasant reovirus detected recently in the United States. Additionally, we found that Reo/HUN/Pheasant/216/2015 is a multi-reassortant reovirus within the species Avian orthoreovirus that shared genetic relationship with turkey reoviruses (σC), partridge reoviruses (λA, σB), and chicken reoviruses (λB, λC, μA, σA, and σNS), in the respective gene phylogenies, whereas two genes (μB and μNS) did not reveal any possible common ancestors. The other isolate, D1996/2/1, was found to be distantly related to previously described reoviruses raising the possibility that it might represent a novel orthoreovirus species or a new genogroup within the newly accepted species, Neoavian orthoreovirus. The genetic diversity among pheasant reoviruses could raise challenges for virus classification as well as for development of molecular diagnostic tools and vaccine based prevention and control measures.